Rancang Bangun Aplikasi Augmented Reality Pemilihan Sepatu Berdasarkan Ukuran Kaki Pengguna - Irsyad Fauzan Noor; Herman Tolle; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Each individual always wants to look as good as possible in public. One thing (outfit) of concern is the shoes. each individual has their own way to fulfill their needs, such as shopping in stores or online. With the ignorance of the buyer in shopping online can lead to problems in the selection of the appropriate shoe size with the size of the foot. therefore, it is necessary to build a system that can help the buyers to know the shoe size that is consistent with the size of the foot. By applying the Augmented Reality (AR) system as one solution to resolve these issues. Augmented Reality is a technology that displays virtual objects in the real world in real time. This study aims to create an android system using augmented reality to display a 3D object to simulate the size of shoes shoes on the feet of the user. This system is built by using some software such as Android Studio, Autodesk 3ds Max, Unity 3D, and Vuforia. The system works by scanning the marker is determined and printed on a sheet of paper. If the marker is detected by the system, 3D objects such as shoes will appear on the screen. The results of this study are based on android augmented reality systems can help users in knowing the shoe size in real time.